2019
DOI: 10.1002/ldr.3426
|View full text |Cite
|
Sign up to set email alerts
|

Continuous grass coverage as a management practice in humid environment vineyards increases compaction and CO2 emissions but does not modify must quality

Abstract: Few works have been carried out on the coupled impacts of different management practices and tractor traffic on soil properties and degradation in vineyards, grape productivity and must quality. The influence of different tillage practices (conventional tillage—CT; grass coverage in a given year—INV‐GC; tillage in a given year—INV‐T) and continuous grass coverage (CGC) on bulk density (BD), soil water content (SWC), CO2 emissions, grape yield and must quality have been investigated in a vineyard in Zagreb, Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Conventional tillage often decreases the bulk density of soil in the early stages of plant growth [44]. However, until the end of the vegetation season, the compaction level in conventional tillage systems is several times higher due to settling, unstable soil structure, and additional traffic events [48,49]. Our results were consistent with previous studies that reported higher compaction under conventionally plowed than under conservation loosening tillage [21,37,50].…”
Section: Impact On Soil Propertiessupporting
confidence: 90%
“…Conventional tillage often decreases the bulk density of soil in the early stages of plant growth [44]. However, until the end of the vegetation season, the compaction level in conventional tillage systems is several times higher due to settling, unstable soil structure, and additional traffic events [48,49]. Our results were consistent with previous studies that reported higher compaction under conventionally plowed than under conservation loosening tillage [21,37,50].…”
Section: Impact On Soil Propertiessupporting
confidence: 90%
“…al., 2018). In this study case, lower BD (Figure 2A) in GCV was observed in addition to the TV due to the long period of grass-covering which was found to decrease BD in the cases where this management was longterm (Bogunovic et al, 2019a). Additionally, treatment differences were attributed to the management, since the absence of machinery traffic on the soil did not impact soil compaction (Lipiec et al, 2007;Bogunovic et al, 2019a).…”
Section: Soil Propertiesmentioning
confidence: 58%
“…Generally, a decrease of the bulk density (BD) can be observed following tillage (Bogunovic et al, 2017), but those effects are temporary as the soil consolidates with time (Alletto and Coquet, 2009;Al-Jabri et al, 2016). Additionally, traffic highly increases BD in vineyards (Ferrero et al, 2007;Bogunovic et al, 2019a) and distorts soil structure (de Lima et al, 2017). Tillage and traffic-induced changes in BD and soil structure modifies soil hydraulic properties (Horton et al, 1994;Dec et al, 2008;Strudley et al 2008) and increase overland flow (Bogunovic et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting higher soil water content and stronger vegetation with higher root biomass can further modify soil CO 2 emission. The type of vegetation and the cover crop can also significantly impact soil CO 2 emissions [23]. Simultaneously, biochars have high potential to sequester carbon, thus reducing soil CO 2 emission [24,25].…”
Section: Introductionmentioning
confidence: 99%